Neutrophil and eosinophil involvement of the small bowel affected by chronic alcoholism. Issue 12 (December 1988) - Colombel, J F; Hällgren, R; Venge, P; Mesnard, B; Rambaud, J C
Abstract : Excessive ethanol intake may affect the intestinal mucosa functionally and morphologically. The ethanol effect could partly be the result of inflammatory mechanisms, possibly reflected by an enhanced local granulocyte turnover. This study investigated habitual alcoholics by segmental perfusion of the jejunum and analysed the perfusion fluid content of granulocyte granule constituents. The mean jejunal secretion rate of myeloperoxidase (MPO), a neutrophil granule constituent, was 152 (26) (SE) ng/min/40 cm jejunal segment in the controls (n = 16). The MPO secretion rate in non-cirrhotic habitual alcoholics (n = 7) was on average 450 (103) ng/min and significantly increased compared with controls (p less than 0.001). In contrast alcoholics with cirrhosis (n = 6) had normal MPO secretion rate. The mean secretion rate of eosinophil cationic protein (ECP), an eosinophil granule constituent, was in the controls 77 (15) ng/min/40 cm jejunal segment. Corresponding values in non-cirrhotic and cirrhotic alcoholics were 141 (38) and 130 (93) ng/min, respectively (ns). The data suggest an enhanced neutrophil granulocyte turnover in the jejunum in alcoholics, possibly contributing to the ethanol induced affection of the small bowel. The lack of increased neutrophil activity in cirrhotic alcoholics may reflect a role of the liver for granulocyte activity.